Treatment of obstructive sleep apnea does not treat primary nocturnal enuresis. Issue 2 (April 2021) - Davaro, Facundo; Kaba, Aboubacar; Osei, Hector; Joshi, Parth; Hamilton, Zachary; Phillips, Timothy
Summary: Introduction: Primary Nocturnal Enuresis (PNE), obesity, and obstructive sleep apnea (OSA) are suggested to share a complex interaction whereby risk for PNE is increased when obesity and airway obstruction are present. We aimed to evaluate whether surgical or medical management of OSA in the treatment of patients with PNE and improves PNE outcomes. Study design: Our institutions electronic medical record was queried for patients who underwent a pediatric diagnostic polysomnogram (PDPSG) for the complaint of PNE between October 2010 and September 2020 and were diagnosed with OSA. Retrospective chart review was performed of the 59 patients identified. Patients were divided based on therapy type for their OSA. Groups included those no therapy, any therapy which includes patients undergoing tonsillectomy and adenoidectomy (T&A) and/or continuous positive airway pressure (CPAP) and those who chose T&A. Primary outcome was to evaluate effects of treating OSA with T&A and effects on PNE outcome based on International Children's Continence Society (ICCS) definitions of complete, partial or no improvement. Separate grouping based on ICCS PNE outcome were also made for evaluation of variables associated with each group. Secondary outcome evaluated role of BMI in success of treatments of PNE. Chi-squared and one-way ANOVA tests were performed. Results: 59 patients (64.4% male, mean age at diagnosis 8.8 years old) underwent a PDPSG for PNE. Monosymptomatic PNE was diagnosed in 40.7% while 32.2% had non-monosymptomatic PNE and the remainder were unknown. Patients were predominantly Caucasian (47.5%), with an average BMI of 20.6 kg/m 2 25 patients underwent no therapy for their OSA while the remaining 34 received treatment. No statistically significant difference between those receiving and those forgoing therapy were noted in age, race, gender, BMI, type of PNE or Apnea-Hypopnea Index. There was also so significant difference in ICCS defined enuresis outcomes (p = 0.871) with over 60% in both groups experiencing resolution or improvement. Follow up was significantly different between cohorts, measured at 43 months for those receiving therapy for OSA and 29.1 months for those forgoing therapy. When considering only those who chose T&A as their therapy for PNE, there were once again, no significant differences between groups including ICCS enuresis outcome. Sub-grouping based on ICCS enuresis outcome revealed no associations between variables measured and improvement of PNE (p > 0.05), other than defining type of PNE (p = 0.012). Conclusion: In patients with OSA and PNE, surgical treatment of airway obstruction had no effect on resolution of PNE. Summary Table No Therapy versus Any Therapy, versus T&A for PNE Summary Table Variable No Therapy (n = 25) Any Therapy a (n = 34) p-value T&A (n = 25) p-value Mean Age 8.6 ± 2.9 8.9 ± 3.5 0.772 8.8 ± 3.7 0.875 Type of PNE 0.073 0.204 Monosymptomatic 7 (28.0%) 17 (50.0%) 11 (44.0%) Non-Monosymptomatic 12 (48.0%) 7 (20.6%) 6 (24.0%) Unknown 6 (24.0%) 10 (29.4%) 8 (32.0%) Gender 1.000 1.000 Male 16 (64.0%) 22 (64.7%) 15 (60.0%) Female 9 (36.0%) 12 (35.3%) 10 (40.0%) Race 0.964 0.993 White 11 (44.0%) 17 (50.0%) 12 (48.0%) Black 11 (44.0%) 14 (41.2%) 10 (40.0%) Other 3 (12.0%) 3 (8.8%) 3 (12.0%) Body Mass Index 20.6 ± 5.9 20.6 ± 6.3 0.994 21.0 ± 6.3 0.802 Apnea-Hypopnea Index 4.1 ± 3.4 5.4 ± 3.8 0.188 5.2 ± 3.7 0.281 PNE Outcome 0.871 0.810 Complete/Partial Improvement 17 (68.0%) 21 (61.7%) 15 (60.0%) No Improvement 8 (32.0%) 13 (38.3%) 10 (40.0%) Follow up 29.1 ± 20.6 43.0 ± 25.6 0.032 44.5 ± 25.6 0.025 ∗PNE= Primary Nocturnal Enuresis, OSA= Obstructive Sleep Apnea, CPAP= Continuous-Positive Airway. Pressure, T&A = Tonsillectomy and Adenoidectomy. a Any therapy is defined as CPAP and/or T&A.